Eine deskriptive Analyse der Verteilung von Online-Bewertungen auf digitalen B2B-Märkten - Petrovic, Bogoljub

Eine semantische Analyse von Online-Bewertungen auf digitalen B2B-Märkten - Schulte, Tristan Aaron

Entwicklung eines Rahmenwerks zur Evaluation von Geschäftsmodellen zur Entscheidungsunterstützung für Kooperationen mit Startups am Beispiel der Schüco International KG - Golis, Miriam

Feasibility study on the use of Hypermedia/HATEOAS using an example of a RESTful API from the financial services environment based on OpenAPI/Swagger - Brockmeier, Felix Karl

Mechanismen zur Aggregation der Meinungen einer Crowd - Ein klassifizierender Literaturüberblick - Schiller, Leo

The effects of driver variables on online review metrics: A meta-analysis - Selig, Maximilian Julius

Share at all Costs? Ein Literaturüberblick zur Privacy Risk Calculus Theory - Althaus, Maike

Sozioökonomische Implikationen des Sharing Economy Trends - Rohde, Lukas

Reputation in der Sharing Economy - Eine ökonometrische Analyse des Zusammenhangs zwischen Online-Bewertungen und Nachfrage am Beispiel von Airbnb - Bentfeld, Bastian

Stoppt das Sharing? Ökonometrische Untersuchungen zur gesetzlichen Einschränkung von Airbnb - Agethen, Christopher Heinrich

It's a match! - Entwicklung eines Ansatzes zur Identifikation von Cross-Listings auf Airbnb und TripAdvisor - Wegener, Moritz

Do Online Ratings Matter in the Sharing Economy? Analyzing the Impact of Online Ratings on Demand on Airbnb - Gerzen, Gabriele

Möglichkeiten und Grenzen crowdbasierter Ideenbewertung - Ein systematischer Literaturüberblick - Resch, Tim

Externe Stimuli zur Geschäftsmodell-Ideengenerierung: Ein Experimenteller Ansatz - Milder, Christoph

Blätterwald zur Positionierung in akademischen Texten - Karsten, Andrea (Praxishandbuch Schreibdidaktik. Übungen zur Vermittlung wissenschaftlicher Schreibkompetenzen)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)
RbInSe2 is attracting growing interest as a secondary semiconductor compound in Cu(In,Ga)Se2-based solar cells by virtue of the recent investigations on absorber post-deposition treatments with alkali metal salts that have resulted in significant efficiency improvements. However, the detection of the RbInSe2 phase on the surface of chalcopyrite absorbers is very challenging due to its nanometric thickness and the limited information available about its fundamental properties. In this context, this work expounds a detailed analysis of the vibrational properties of RbInSe2 that combines first-principle calculations with multiwavelength Raman scattering spectroscopy and provides a methodology for the detection and identification of very thin layers of this material employing solely optical measurements. As a result, here, we present the classification of the different vibrational modes together with the fingerprint Raman spectra of RbInSe2 thin films measured under five different excitations (close to and far from resonance). The employment of a 442 nm excitation wavelength is found to be the most adequate strategy for the detection and characterization of the RbInSe2 phase in view of its resonance with the band gap of the material and its low penetration depth. Additionally, the purity of the deposited thin films as well as the possible influence of the subjacent layers on the Raman spectra of the compound are also investigated by analyzing the presence of secondary phases and by measuring RbInSe2 thin films deposited onto Mo-coated soda-lime glass, respectively. These results set the basis for the future evaluation of the suitability of Raman spectroscopy as a fast and nondestructive characterization technique for the reliable identification and characterization of the nanometric layers of RbInSe2 in Cu(In,Ga)Se2-based solar cells.

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas D.; Mirhosseini, Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas; Mirhosseini, S. Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Alkali Atoms Diffusion Mechanism in CuInSe 2 Explained by Kinetic Monte Carlo Simulations - Kormath Madam Raghupathy, Ramya; Kühne, Thomas; Henkelman, Graeme; Mirhosseini, Hossein (Advanced Theory and Simulations)
Adaptive kinetic Monte Carlo simulation (aKMC) is employed to study the dynamics and the diffusion of point defects in the CuInSe2 lattice. The aKMC results show that lighter alkali atoms can diffuse into the CuInSe2 grains, whereas the diffusion of heavier alkali atoms is limited to the Cu-poor region of the absorber. The key difference between the diffusion of lighter and heavier alkali elements is the energy barrier of the ion exchange between alkali interstitial atoms and Cu. For lighter alkali atoms like Na, the interstitial diffusion and the ion-exchange mechanism have comparable energy barriers. Therefore, Na interstitial atoms can diffuse into the grains and replace Cu atoms in the CuInSe2 lattice. In contrast to Na, the ion-exchange mechanism occurs spontaneously for heavier alkali atoms like Rb and the further diffusion of these atoms depends on the availability of Cu vacancies. The outdiffusion of alkali substitutional atoms from the grains results in the formation of Cu vacancies which in turn increases the hole concentration in the absorber. In this respect, Na is more efficient than Rb due to the higher concentration of Na substitutional defects in the CuInSe2 grains.

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game